2008
DOI: 10.1029/2007wr006522
|View full text |Cite
|
Sign up to set email alerts
|

Wood dynamics in headwater streams of the Colorado Rocky Mountains

Abstract: [1] An 11-year monitoring study begun in 1996 evaluates wood mobility in five Colorado Rocky Mountain streams. Each channel reach is 40-70 m in length. Initial surveys included channel dimensions and arrangement of each piece of wood. Annual resurveys focused on wood arrangement and persistence. Average diameter of 15 cm and length of 3.2 m varied little among sites. Average yearly mobility ranged from 16% to 23%. Average residence time was 3.4 years. Wood load correlates positively with valley width and chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
163
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 148 publications
(176 citation statements)
references
References 43 publications
6
163
0
7
Order By: Relevance
“…Burial and unburial can remove or return a substantial amount of wood to streams [Latterell and Naiman, 2007]. Although few studies have considered the effects of burial on mobilization, when burial is included in analyses, it is of primary importance [Berg et al, 1998;Wohl and Goode, 2008]. Our study demonstrated the importance of burial to mobilization using a quantitative analysis and a large number (865) of wood pieces.…”
Section: Controls Of Mobilizationmentioning
confidence: 86%
See 4 more Smart Citations
“…Burial and unburial can remove or return a substantial amount of wood to streams [Latterell and Naiman, 2007]. Although few studies have considered the effects of burial on mobilization, when burial is included in analyses, it is of primary importance [Berg et al, 1998;Wohl and Goode, 2008]. Our study demonstrated the importance of burial to mobilization using a quantitative analysis and a large number (865) of wood pieces.…”
Section: Controls Of Mobilizationmentioning
confidence: 86%
“…At the 10 m scale, the length ratio may relate to the probability that a piece becomes braced before it can escape the 10 m section. Most previous studies have likewise found a negative relationship between length ratios and mobilization [Bilby, 1984;Lienkaemper and Swanson, 1987;Berg et al, 1998;Jacobsen et al, 1999;Gurnell et al, 2002;Hassan et al, 2005;Warren andKraft, 2008, but see Wohl andGoode, 2008]. Finally, we used the effective channel width (i.e., the unobstructed wetted width available to transport wood) to determine our length ratio rather than bankfull width or wetted width.…”
Section: Controls Of Mobilizationmentioning
confidence: 99%
See 3 more Smart Citations